Request for clarification on catwalk and auditorium structure and spiral staircase - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding request for clarification on catwalk and auditorium structure and spiral staircase of BRAC University new campus project.